2020
DOI: 10.1002/elan.202000045
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Multi‐walled Carbon Nanotube‐based Solid Contact Potassium Ion‐selective Electrodes with Reproducible Standard Potentials. A Comparative Study

Abstract: The two most promising approaches for preparing solid contacts (SCs) for polymeric membrane based ion‐selective electrodes (ISEs) are based on the use of large surface areas conducting materials with high capacitance (e. g., various carbon nanotubes) and redox active materials (e. g. conducting polymers). While many of the essential requirements for the potential stability of SCISEs were addressed, the E0 reproducibility and its predictability, that would enable single use of such electrodes without calibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…Long-term impacts of biofouling on the ISM surface were determined using the Nyquist plots of EIS during the continuous 55 day tests. Before being submerged into the wastewater (day 0), the predominant feature for both the conventional S-ISE sensor and the PTFEMA-r-SBMA-loaded S-ISE sensor exhibited a single semicircle as previous reported, 53,54 representing the bulk resistance of the ISM (R S in the equivalent circuit models, Figure 4a,b). After 30 days in wastewater, the conventional S-ISE sensor displayed two bulk resistances, with one from the ISM and the other from biofilm formation.…”
Section: Resultssupporting
confidence: 67%
“…Long-term impacts of biofouling on the ISM surface were determined using the Nyquist plots of EIS during the continuous 55 day tests. Before being submerged into the wastewater (day 0), the predominant feature for both the conventional S-ISE sensor and the PTFEMA-r-SBMA-loaded S-ISE sensor exhibited a single semicircle as previous reported, 53,54 representing the bulk resistance of the ISM (R S in the equivalent circuit models, Figure 4a,b). After 30 days in wastewater, the conventional S-ISE sensor displayed two bulk resistances, with one from the ISM and the other from biofilm formation.…”
Section: Resultssupporting
confidence: 67%
“… 44 The areal capacitance was calculated from the impedance values in the low-frequency (10–100 mHz) part of the EIS spectrum, where the capacitive behavior is dominant. We found that the areal capacitance (29.7 mF cm –2 ) improved considerably compared to other modified MWCNTs such as octadecylamine-modified MWCNTs (7.66 mF cm –2 ) 33 and ferrocene-functionalized MWCNTs (12.33 mF cm –2 ). 37 Chronopotentiometric reverse pulse experiments 9 ( Figure S2 ) confirmed the high capacitance proving also the very low polarizability of the TEMPO-MWCNT-based SCISEs (0.8 mV min –1 ) compared to “coated-wire” electrodes (229.8 mV min –1 ), using the very same composition K + -selective membrane.…”
Section: Resultsmentioning
confidence: 77%
“…Papp et al presented a study on the E 0 reproducibility of solid contact potassium-selective electrodes with octadecane functionalized multiwalled carbon nanotubes (f-MWCNTs) as the transducer layer . They showed that f-MWCNTs provide a relatively small standard deviation of the E 0 value (±5 mV, n = 6) and that this value can be further lowered by external polarization (±2 mV, n = 5) or short circuiting of the ISEs (±1.5 mV, n = 6).…”
Section: Sensor Materialsmentioning
confidence: 99%
“…Papp et al presented a study on the E 0 reproducibility of solid contact potassium-selective electrodes with octadecane functionalized multiwalled carbon nanotubes (f-MWCNTs) as the transducer layer. 81 They showed that f-MWCNTs provide a relatively small standard deviation of the E 0 value (±5 mV, n = 6) and that this value can be further lowered by external polarization (±2 mV, n = 5) or short circuiting of the ISEs (±1.5 mV, n = 6). An external polarization and short circuiting of the ISEs were previously demonstrated to improve the reproducibility of the E 0 value of ISEs with conductive polymers as a solid contact, but the same approach had not been tested before for capacitive materials as MWCNTs.…”
Section: ■ Sensor Materialsmentioning
confidence: 99%